Preschool Gender-Typed Play Behavior Predicts Adolescent Gender-Typed Occupational Interests: A 10-Year Longitudinal Study. - Kung, Karson T. F. (Archives of Sexual Behavior, 2021)
There are significant gender differences in both play behavior and occupational interests. Play has been regarded as an important medium for development of skills and personal characteristics. Play may also influence subsequent preferences through social and cognitive processes involved in gender development. The present study investigated the association between gender-typed play behavior in early childhood and gender-typed occupational interests in early adolescence. Participants were drawn from a British longitudinal population study, the Avon Longitudinal Study of Parents and Children. Participants were recruited based on their parent-reported gender-typed play behavior assessed at age 3.5 years. There were 66 masculine boys and 61 masculine girls, 82 feminine boys and 69 feminine girls, and 55 randomly selected control boys and 67 randomly selected control girls. At age 13 years, the participants were administered a questionnaire assessing their interest in gender-typed occupations. It was found that masculine children showed significantly more interest in male-typical occupations than did control or feminine children. Compared with control children, feminine children had marginally significantly lower interest in male-typical jobs. Masculine children also had significantly lower interest in female-typical jobs than did control or feminine children. The associations were not moderated by gender and were observed after taking into account sociodemographic background, parental occupations, and academic performance. The degree of gender-typed play shown by preschoolers can predict their occupational interests 10 years later following transition into adolescence. Childhood gender-typed play has occupational implications that transcend developmental stages.